PENERAPAN TABUNGAN IB HIJRAH RENCANA SEBAGAI ALTERNATIF PELUNASAN BIAYA HAJI PADA PT. BANK MUAMALAT INDONESIA, KANTOR CABANG PEMBANTU MADIUN - Sofianiyatin, Lilik; Pradana, Aldo Robby (Fakultas Ekonomi Bisnis Islam, 2024)
The researcher focused the research on: Procedures for opening the iB Hijrah Plan Savings and Implementation of the iB Hijrah Plan Savings as an alternative for paying off Hajj expenses at PT. Bank Muamalat Indonesia, Sub-Branch Office. Madiun This research uses qualitative data analysis methods. Where all data obtained through observation and interviews will be collected first, then an analysis process will be carried out and then interpretation will be carried out. The procedure is that the customer comes to the Bank Muamalat office and conveys his goal of opening a savings plan, then after Customer Service validates the customer makes an initial deposit and receives a savings book along with an ATM. The application of iB Hijrah Hajj Savings as an alternative to paying off Hajj expenses means that every month the customer uses an auto-debit system from the main account to the planned savings account. After the funds have been collected, the prospective Hajj pilgrims can pay off the Hajj expenses and if there is still a remaining balance, the customer must take it from the savings account. the plan will close automatically when it is due.